(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article focuses on the development of a set of special exercises aimed at improving the physical fitness of female football referees and evaluating its effectiveness.